INTRODUCTION IN INDONESIAN SOCIAL SCIENCES AND HUMANITIES RESEARCH ARTICLES: HOW INDONESIAN WRITERS JUSTIFY THEIR RESEARCH PROJECTS - Arsyad, Safnil (Linguistik Indonesia, 2014)
The introductory part of a research article (RA) is very important because in this section writers must argue about the importance of their research topic and project so that they can attract their readers’ attention to read the whole article. This study analyzes RA introductions written by Indonesian writers in social sciences and humanities journals. It focuses on how they justify their research topics and research projects. A corpus of 200 research articles written in Indonesian by Indonesian writers and published in Indonesian research journals was analyzed in this study. Following the problem justifying project (PJP) model suggested by Arsyad (2001), the analyses were conducted by using the genre-based analysis of text communicative purpose of ‘move’ and ‘step’. The result of this study indicates that Indonesian writers justify their research project by introducing the actual research topic, identifying the research problem, and reviewing the current knowledge and practices.